Libraries in a digital age: fundamentals and latest thinking - an introduction - Law, Derek (Henry Stewart Talks, 2012)
The education environment, Digital libraries, Changing users, Digital natives -Changing research patterns, Born digital content, Failure of librarians, Adding value, Social networking, Content aggregation, Content curation, Green libraries, Staff skills, Trust metrics, Information retrieval skills